Guillain Barré syndrome precipitated by the use of antilymphocyte globulin in the treatment of severe aplastic anaemia. Issue 9 (26th August 2005) - Kaya, B; Davies, C E; Oakervee, H E; Silver, N C; Gawler, J; Cavenagh, J D
Abstract : This report describes the case of a 54 year old woman with very severe aplastic anaemia who was treated with antilymphocyte globulin (ALG) and developed Guillain Barré syndrome (GBS). No antecedent infective aetiology was identified. Although there are numerous reports of autoimmune disease after treatment with ALG in aplastic anaemia, and GBS after immunosuppressive treatment, there are none reporting GBS after the use of ALG for severe aplastic anaemia. The occurrence of autoimmune disease after immunosuppressive treatment, in particular ALG, is discussed, together with the possible mechanisms that result from T cell depression.